Agency, Cultural Consonance and Depressive Symptoms: A Brazilian Example. (21st May 2019) - Dressler, William W.; Balieiro, Mauro C.; dos Santos, José Ernesto
Abstract: Cultural consonance, or individual enactment of cultural models, is associated with lower depressive symptoms. This article incorporates individual agency into the cultural consonance model. Data were collected using mixed methods in Ribeirão Preto, Brazil. Brazil is a unique setting for this research, given that personal agency is institutionalized in the practice of o jeitinho (a distinctively Brazilian way of circumventing rules). Cultural consonance was measured relative to cultural models of life goals. A measure of a sense of personal agency combined scales of locus of control and frustration tolerance. Cultural consonance had a stronger association with depressive symptoms than individual agency. These results are also consistent with cultural consonance as a mediator of the association of agency and depressive symptoms. The implications for the conceptualization of culture and its role in mental health, and for the influence of psychological factors on culture, are discussed. [Brazil, agency, cultural consonance, depression]